2019
DOI: 10.1371/journal.pone.0220811
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation effects of two types of freeway deceleration markings in China

Abstract: This paper presents an evaluation of the effectiveness of two types of deceleration markings on freeways in China: fishbone-shaped (FS) markings and edge-rate (ER) markings. An actual 4-lane, 6-km long freeway in Province Hebei was created in a driving simulator and used for the experiments. Three scenarios of deceleration markings were adopted: one without markings, one with FS markings, and the third with ER markings. For each scenario, three traffic flow levels were adopted (low, medium, and heavy). The app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The objective was to investigate the impact of sign content and word count restrictions on the layout. Simulation experiments were conducted using a driving simulator and an eye-tracking device to assess the effectiveness of utilizing two distinct shapes of deceleration signs for conveying sign messages [59]. Furthermore, the effectiveness of the scheme for exit warning signs in mountain tunnels was evaluated using the aforementioned simulation experiments and eye-tracking technique.…”
Section: Eye-tracking Technology Application For Sign Layout Optimiza...mentioning
confidence: 99%
“…The objective was to investigate the impact of sign content and word count restrictions on the layout. Simulation experiments were conducted using a driving simulator and an eye-tracking device to assess the effectiveness of utilizing two distinct shapes of deceleration signs for conveying sign messages [59]. Furthermore, the effectiveness of the scheme for exit warning signs in mountain tunnels was evaluated using the aforementioned simulation experiments and eye-tracking technique.…”
Section: Eye-tracking Technology Application For Sign Layout Optimiza...mentioning
confidence: 99%
“…Lee et al [60] observed a significant reduction in the average driving speed of the vehicles at the ramps of expressways by using transverse pavement marking and thus consequently found a reduction in accident frequency. Yang et al [61] compared the effect of traditional marking, fishbone-shaped marking and edge-rate marking on the speed reduction of vehicles at the expressway's deceleration lane and found that fishbone-shaped marking was effective in reducing vehicles speed from 12.3 km/h to 15.2 km/h. [11,30,47] have tried to understand the interaction effect of risk factors on accident frequency.…”
Section: Some Other Variablesmentioning
confidence: 99%
“…In a virtual simulation, the environment is depicted on a screen, while in VR the environment is generated through an HMD. The driving simulator in the writer's lab at Ryerson University was used to model and analyze numerous aspects related to road safety, driver mental workload, traffic operations, and in-vehicle collision warning systems [11][12][13][14]. Note that a driving simulator can include the use of an HMD as its primary input-output equipment.…”
Section: What Is Virtual Reality?mentioning
confidence: 99%